Fish harvesting management strategies using logistic growth model (Strategi Pengurusan Penuaian Ikan dengan Menggunakan Model Pertumbuhan Logistik) - Mohamed Faris Laham; Ishtrinayagy S. Krishnarajah; Jamilah Mohd. Shariff (Universiti Kebangsaan Malaysia, 2012)
This paper studies the harvesting strategies for tilapia fish farming. Two logistic growth models have been used namely constant harvesting and periodic harvesting. Even though tilapia fish farming has been commercialized, the use of mathematical models in determining harvesting strategies has not been widely applied in Malaysia. Logistic growth model is appropriate for population growth of animal when overcrowding and competition resources are taken into consideration. The objectives of this study were to estimate the highest continuing yield from fish harvesting strategies implemented. Secondly, the study predicted the optimum quantity for harvesting that can ensure the tilapia fish supply is continuous. Finally, to compare the results obtained between the two strategies. The best harvesting strategy for the selected fish farm is periodic harvesting. These findings can assist fish farmers to increase the supply to meet the demand for tilapia fish.